2022
DOI: 10.3390/land11111949
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Comprehensive Development Level and Coordinated Relationships of Urban Multimodal Transportation: A Case Study of China’s Major Cities

Abstract: Urban multimodal transportation effectively meets the diversified travel demand of residents. However, it also generates extensive development problems such as traffic congestion, exhaust emissions and low operational efficiency. Therefore, there is an urgent need in urban sustainable development to achieve the coordinated and stable development of various modes of transportation. In this study, we took 36 major cities in China as the research object; measured the comprehensive development level of urban multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…In order to study the level of CCD between FT and LM, the study referred to relevant research [50], and constructed the coupling coordination degree model (CCDM). The formula can be described by Equations ( 9)-( 11):…”
Section: Ccdmmentioning
confidence: 99%
“…In order to study the level of CCD between FT and LM, the study referred to relevant research [50], and constructed the coupling coordination degree model (CCDM). The formula can be described by Equations ( 9)-( 11):…”
Section: Ccdmmentioning
confidence: 99%
“…Furthermore, it has been shown that complete multimodal transport and the relationship between multi-layered networks are essential for a comprehensive understanding of urban transport systems [35]. Understanding the relationship between urban multimodal transport development is conducive to coordinating the relationship between traffic and land use and alleviating urban traffic congestion [36]. Current research on multi-level transportation networks has focused on the relationship between passenger flow distribution and network characteristics [37], for example, by establishing a simple relationship between passenger flow and route length as a way to assess the change in passenger flow after integration between subway and bus systems [38].…”
Section: Introductionmentioning
confidence: 99%